Hybrid AHP TOPSIS Approach for Evaluating Green Supply Chain Management Barriers in the Poultry Processing Industry - Asrul Fole; Khoerun Nisa Safitri; Nurul 'Aini; Erniyani; Bili Syufrian (Cognitia : International Engineering Journal, 2026)
The implementation of Green Supply Chain Management (GSCM) has become increasingly important in the agro-industrial sector, particularly in the poultry processing industry, due to rising environmental concerns and growing demand for sustainable production practices. However, its adoption remains limited because of various operational, technological, and managerial barriers. This study aims to identify and evaluate the major barriers to GSCM implementation and determine the most appropriate strategic solutions using a hybrid multi-criteria decision-making approach. The methods applied combine the Analytical Hierarchy Process (AHP) to assess the priority weights of barriers and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to rank alternative strategies. Data were collected through literature review, expert validation, and questionnaires distributed to 37 respondents involved in poultry supply chain activities, with all instruments proven valid and reliable. The findings reveal five primary barriers, namely limited environmentally friendly technology, low management commitment, limited investment capacity, inadequate human resource training, and unclear regulatory support and incentives. The TOPSIS analysis indicates that training and awareness enhancement is the most effective strategy, achieving the highest closeness coefficient value of 0.812. The study concludes that strengthening internal organizational capabilities, particularly through training and awareness, along with improving external support mechanisms, is essential to facilitate effective and sustainable GSCM implementation in the agro-industrial sector.